Relationship Between Religion and Science: Analysis of Darussalam Gontor University Response to Covid-19 - Sufratman Sufratman; Asep Awaludin; Herianti Herianti (IAIN Padangsidimpuan, 2022)
This paper aims to analyze the nature of the relationship between religion and science applied by UNIDA Gontor, especially the policy in dealing with the Covid-19 pandemic. This is done, at least for two reasons. First, UNIDA Gontor is the only higher education institution in the country that continues to carry out normal activities in the midst of the Covid-19 pandemic. Second, UNIDA Gontor is an Islamic educational institution based on Islamic boarding schools. As library research, this paper uses a descriptive method. The results can be concluded that there are at least four patterns in building the relationship between religion and science: conflict, independence, dialogue, and integration. UNIDA Gontor uses an Integration model with the Islamization of knowledge in dealing with the Covid-19 pandemic. This is because UNIDA Gontor applies ihktiar al-diniyyah and al-ilmiyyah at the same time preventing the spread of Covid-19 infection. The two pledges were integrated within the framework of an Islamic worldview, thus, giving rise to three forms of strategic policies, namely; First, form a Covid-19 task force; second, involve elements of the government and IKPM Gontor; and the third, self-isolation. By consistently implementing these efforts, the entire academic community and students in the UNIDA Gontor environment can avoid and function normally even in the midst of the Covid-19 virus infection